Minimal projection onto certain subspace of Lp(X×Y×Z). (3rd October 2018) - Kozdęba, Michał
Abstract: Let X, Y, Z be Banach spaces. We show a formula for a minimal projection fromS = L p ( X × Y × Z ) ontoT = L p ( X × Y ) + L p ( X × Z ) + L p ( Y × Z ) . It is a generalization of a result of Cheney and Light who showed a formula for a minimal projection fromS = L p ( X × Y ) ontoT = L p ( X ) + L p ( Y ) .